Evidence-base for aspirin as venous thromboembolic prophylaxis following joint replacement. Issue 5 (May 2014) - Jameson, S. S.; Baker, P. N.; Deehan, D. J.; Port, A.; Reed, M. R.
Abstract : The National Institute for Health and Clinical Excellence (NICE) has thus far relied on historical data and predominantly industry-sponsored trials to provide evidence for venous thromboembolic (VTE) prophylaxis in joint replacement patients. We argue that the NICE guidelines may be reliant on assumptions that are in need of revision. Following the publication of large scale, independent observational studies showing little difference between low-molecular-weight heparins and aspirin, and recent changes to the guidance provided by other international bodies, should NICE reconsider their recommendations? Cite this article: Bone Joint Res 2014;3:146–9.